Immune response against antibiotic-resistant and antibiotic-sensitive staphylococcus aureus in a rat model of implant infection - Yingfang Fan; Amita Sekar; Madeline McCanne; Jean Yuh; Devika Dutta Kannambadi; Sashank Lekkala; Orhun K. Muratoglu; Ebru Oral (Scientific Reports)
Abstract Little is known about the in-vivo dynamics of biofilms associated with medical-device infections and their interplay with systemic inflammation, local immune responses, and tissue healing processes. There may be an opportunity to tailor therapeutic strategies to target these dynamics to improve treatment outcomes. We investigated immune responses to a methicillin-susceptible (ATCC 12600) and a multi-drug resistant (L1101) S. aureus strain using a rat subcutaneous implant model, analyzing local and systemic inflammation through 19 gene expressions over 21 days. Our goals were to identify differences in the immune response due to infection and also with respect to the two strains. We observed that systemic inflammation, indicated by α-2-macroglobulin, was elevated in the initial stages (up to day 7). Local inflammatory cytokine levels (IL-6, TNF-α, IL-6, TNF-α, IL-1β, IL10, IL-17, IL12a, IL12b, I F NG) varied by strain, typically higher against the clinical strain. Infections generally hindered early macrophage (MCSF1) and T-cell (CD4, CD5, CD6, CD8 A) recruitment, particularly in cases involving the clinical strain. Conversely, a better healing response was observed in the infection of the more susceptible ATCC 12600 strain (VEGF, CXCR1, CXCR2, MMP-1, MMP-3, MMP-13). These results are crucial for understanding immune responses to such infections, guiding therapeutic strategies.